Sorting within and across establishments: The immigrant-native wage differential in Germany - Mario Bossler (Institut für Arbeitsmarkt- und Berufsforschung (IAB), 2014)
Using new and unique linked employer-employee data from Germany, I examine the extent to which immigrants sort into worse-paying establishments and worse job positions within establishments. The results demonstrate that recent immigrants are particularly likely to work at low-paying workplaces. Similarly, when examining job positions within establishments, I find that immigrants are employed in lower hierarchical positions. Both the non-random sorting across establishments and the hierarchical sorting within establishments explain much of the immigrant-native wage differential. Policy measures designed to address the wage differential should therefore address immigrants' access to well-paying workplaces and job positions. With respect to career development, immigrant participation in performance assessments is low, and immigrants feel disadvantaged in personnel decisions, which in turn might be relevant channels that explain immigrants' under-representation in well-paid positions. – – Unter Verwendung des neuen Linked Personnel Panels (LPP) untersuche ich das Ausmaß der Beschäftigung von Migranten in schlecht bezahlenden Betrieben und Jobs. Die Ergebnisse zeigen, dass insbesondere kürzlich migrierte Personen in schlechter bezahlenden Betrieben arbeiten. In Bezug auf die Job-Hierarchie zeigt sich, dass Migranten in niedrigeren Positionen beschäftigt sind. Lohnregressionen ergeben den Befund, dass die negative Selektion in schlechter bezahlte Jobs und zu schlechter bezahlenden Arbeitgebern einen großen Anteil des Lohnunterschieds zwischen Migranten und Deutschen erklärt. Politikmaßnahmen sollten daher an beiden Dimensionen ansetzen, um eine bessere Integration zu gewährleisten. Vertiefende Analysen hinsichtlich der Personalführung zeigen, dass Migranten seltener an einem Beurteilungsgespräch teilnehmen und sich bei Personalentscheidungen benachteiligt fühlen. Diese Befunde können somit einen relevanten Erklärungsansatz für die niedrige Repräsentation in hohen Positionen darstellen.
Keywords: J31; J61; R71; 330; Sorting; immigrant wage differential; hierarchical job positions